HYPNOSIS LIMA JARI UNTUK MENGATASI DEPRESI, ANSIETAS DAN STRESS PADA MASYARAKAT TERPAPAR BANJIR ROB (STUDI PADA KABUPATEN PEKALONGAN): Five-Fingers Hypnosis To Overcome Depression, Anxiety And Stress In Community Which Are Flooded By Rob (Study In Pekalongan On District) - Aisyah Dzil Kamalah; Hana Nafiah (Journal of Community Mental Health and Public Policy, 2019)
Pekalongan Regency is one of the areas located on the north coast of the Java Sea and occurred rob every year. Psychosocial problems such as anxiety and stress appeared accompanied by depression due to rob that has occurred since 2008. Five-finger hypnosis is a generalist therapy in mental nursing to reduce anxietyby bringing respondents in a relaxed condition and increasing calm by inviting respondents to imagine. This study aims to determine the effect of five-finger hypnosis on depression, anxiety, and stress felt by residents of the village of Jeruksari, Pekalongan Regency affected by rob. The design of this study used quantitative research with a pre-experimental approach with the pretest post-test one-group design method. This research was conducted on30 people. Data collection was carried out with a Depression Anxiety Stress Scale (DASS) questionnaire administered before and after the intervention. five-finger hypnosis therapy, bivariate analysis was performed with a t-test, the t-test results showed a sig value. 0.001 with a significance level of 0.05. This showed that five-finger hypnosis can reduce depression, anxiety, and stress felt by respondents who reside in the Rob Pekalongan district.